Exploring the relationships between computer task characteristics, mental workload, and computer users' biomechanical responses. Issue 9 (2nd September 2022) - Wang, Xueke; Lavender, Steven A.; Sommerich, Carolyn M.; Rayo, Michael F.
Abstract: Previous biomechanics studies suggest that higher cognitive mental workload when performing office computer tasks may increase the risk of MSDs among office workers. Cognitive workload can be interpreted in terms of task factors (e.g. task complexity and time pressure) and mental workload factors which include mental demand and mental effort. A laboratory study was conducted to further explore how the task and mental workload factors affected computer users' biomechanical responses, specifically the muscle activation levels and sitting postures. Data were collected as 20 participants worked on computer tasks which varied in their levels of task complexity and time pressure. Visual analog scales were used for assessing mental workload factors. Results indicated that the level of mental effort reported, as opposed to the level of task complexity, was associated with changes in participants' biomechanical responses, but primarily occurred when the chair's backrest was not used. Practitioner summary: A study was conducted to investigate the association between computer users' cognitive workload and biomechanical responses when performing computer task. While task complexity was not directly associated with the changes in participants' biomechanical responses, higher reported mental effort was associated with increased biomechanical responses, but only when the participants did not use the backrest on the chair.